Behavior of Orius insidiosus preying on Aphis gossypii reared on transgenic and conventional cotton varieties - Veiga, Ana Carolina Pires [UNESP]; Laurentis, Valéria Lucas De [UNESP]; Vacari, Alessandra Marieli [UNESP]; Volpe, Haroldo Xavier Linhares [UNESP]; Ramalho, Dagmara Gomes; Bortoli, Sergio Antonio De [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2014)
The objective of this study was to evaluate the functional response of Orius insidiosus preying on the third and fourth instars of Aphis gossypii nymphs that were reared on transgenic NuOPAL (Bollgard I Event 531) and conventional Buriti cotton varieties. Fifty O. insidiosus female bugs aged 12-24h were distributed into five different Petri dishes with different densities of A. gossypii (2, 4, 8, 16, and 32 nymphs per plate) for each cotton variety. The number of prey consumed was evaluated over the course of 12h, with a final assessment at 24h. The handling times (Th) and attack rates (a) were 0.0697h and 1.1862h-1, respectively, for the Buriti variety and 0.0713h and 0.3030h-1, respectively, for the NuOPAL variety. The average number of prey consumed by O. insidiosus was similar for both varieties at 24h and at higher densities; the attack rate was higher for the Buriti-reared aphid prey than for the NuOPAL-reared aphids.

O objetivo deste estudo foi avaliar a resposta funcional de Orius insidiosus que predaram ninfas de terceiro e quarto instar de Aphis gossypii criadas em variedades de algodão transgênico e convencional. Cinquenta fêmeas de O. insidiosus de 12-24h foram individualizadas por tratamento em placas de Petri. Diferentes densidades de A. gossypii (2, 4, 8, 16 e 32 ninfas por placa) foram testadas usando cada variedade de algodão. O número de presas consumidas foi avaliado durante 12h. Foi realizada uma avaliação final com 24h. O tempo de manipulação (Th) e a taxa de ataque (a) foram 0,0697h e 1,1862h-1, respectivamente, para a variedade Buriti e 0,0713h e 0,3030h-1, respectivamente, para a variedade NuOPAL. O número médio de presas consumidas por O. insidiosus foi similar para ambas variedades com 24h e com maiores densidades; a taxa de ataque foi maior com pulgões criados em Buriti do que criados em NuOPAL.
Comportamento de Orius insidiosus predando Aphis gossypii criados em variedades de algodão transgênico e convencional
Keywords: pulgão do algodoeiro; resposta funcional; Gossypium hirsutum; percevejo pirata; plantas transgênicas; cotton aphid; functional response; Gossypium hirsutum; minute pirate bug; transgenic plants